Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the given expressions, let's evaluate each one step-by-step:
### Expression 1: [tex]\( 5 - 5 \)[/tex]
Evaluate:
[tex]\[ 5 - 5 \][/tex]
Subtract 5 from 5:
[tex]\[ 5 - 5 = 0 \][/tex]
So, the value of the first expression is [tex]\( 0 \)[/tex].
### Expression 2: [tex]\(-5 - (-5)\)[/tex]
Evaluate:
[tex]\[ -5 - (-5) \][/tex]
Subtracting a negative number is the same as adding the positive counterpart:
[tex]\[ -5 - (-5) = -5 + 5 = 0 \][/tex]
So, the value of the second expression is [tex]\( 0 \)[/tex].
### Expression 3: [tex]\(-5 - 5\)[/tex]
Evaluate:
[tex]\[ -5 - 5 \][/tex]
Subtract 5 from -5:
[tex]\[ -5 - 5 = -10 \][/tex]
So, the value of the third expression is [tex]\( -10 \)[/tex].
### Expression 4: [tex]\( 5 - (-5) \)[/tex]
Evaluate:
[tex]\[ 5 - (-5) \][/tex]
Subtracting a negative number is the same as adding the positive counterpart:
[tex]\[ 5 - (-5) = 5 + 5 = 10 \][/tex]
So, the value of the fourth expression is [tex]\( 10 \)[/tex].
Therefore, the complete solutions are:
1. [tex]\( 5 - 5 = 0 \)[/tex]
2. [tex]\(-5 - (-5) = 0 \)[/tex]
3. [tex]\(-5 - 5 = -10 \)[/tex]
4. [tex]\(5 - (-5) = 10 \)[/tex]
Thus, filling in the blanks, we have:
[tex]\[ \begin{array}{l} 5-5=0 \\ -5-(-5)=0 \end{array} \][/tex]
[tex]\[ \begin{array}{l} -5-5=-10 \\ 5-(-5)=10 \end{array} \][/tex]
### Expression 1: [tex]\( 5 - 5 \)[/tex]
Evaluate:
[tex]\[ 5 - 5 \][/tex]
Subtract 5 from 5:
[tex]\[ 5 - 5 = 0 \][/tex]
So, the value of the first expression is [tex]\( 0 \)[/tex].
### Expression 2: [tex]\(-5 - (-5)\)[/tex]
Evaluate:
[tex]\[ -5 - (-5) \][/tex]
Subtracting a negative number is the same as adding the positive counterpart:
[tex]\[ -5 - (-5) = -5 + 5 = 0 \][/tex]
So, the value of the second expression is [tex]\( 0 \)[/tex].
### Expression 3: [tex]\(-5 - 5\)[/tex]
Evaluate:
[tex]\[ -5 - 5 \][/tex]
Subtract 5 from -5:
[tex]\[ -5 - 5 = -10 \][/tex]
So, the value of the third expression is [tex]\( -10 \)[/tex].
### Expression 4: [tex]\( 5 - (-5) \)[/tex]
Evaluate:
[tex]\[ 5 - (-5) \][/tex]
Subtracting a negative number is the same as adding the positive counterpart:
[tex]\[ 5 - (-5) = 5 + 5 = 10 \][/tex]
So, the value of the fourth expression is [tex]\( 10 \)[/tex].
Therefore, the complete solutions are:
1. [tex]\( 5 - 5 = 0 \)[/tex]
2. [tex]\(-5 - (-5) = 0 \)[/tex]
3. [tex]\(-5 - 5 = -10 \)[/tex]
4. [tex]\(5 - (-5) = 10 \)[/tex]
Thus, filling in the blanks, we have:
[tex]\[ \begin{array}{l} 5-5=0 \\ -5-(-5)=0 \end{array} \][/tex]
[tex]\[ \begin{array}{l} -5-5=-10 \\ 5-(-5)=10 \end{array} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.